Two Novel and Two Recurrent Variants of the ADAR1 Gene in Three Chinese Families with Dyschromatosis Symmetrica Hereditaria - Zhu Y; Zhang D; Wu L; Ouyang X; Zhu S; Wang X; Xiao Z; Tan Y; Li C (Dove Medical Press, 2024)
Yunxia Zhu,1 Deng Zhang,1 Liang Wu,1 Xiaoliang Ouyang,2 Shengcai Zhu,1 Xiuping Wang,1 Zhen Xiao,3 Yanping Tan,4 Chunming Li1 1Department of Dermatology, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, People's Republic of China; 2Department of Plastic Surgery, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, People's Republic of China; 3Department of Dermatology, Taiyuan Central Hospital, Taiyuan, Shanxi, People's Republic of China; 4Department of Dermatology, Jiangxi Provincial Maternal and Child Health Hospital, Nanchang, Jiangxi, People's Republic of ChinaCorrespondence: Chunming Li, Department of Dermatology, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, People's Republic of China, Tel/Fax +86 79186278821, Email chunminglincu@163.comPurpose: Dyschromatosis symmetrica hereditaria (DSH) is a rare autosomal dominant inherited pigmentary dermatosis. The gene responsible for DSH has been identified as adenosine deaminase acting on RNA1 (ADAR1). This study aimed to identify the causative variants in the ADAR1 gene in three Chinese families with DSH.Patients and Methods: Data and blood samples were collected from three Chinese families with DSH. Whole-exome and Sanger sequencing were performed to detect pathogenic gene mutation in the patients. Bioinformatics tools were used to predict the pathogenicity of the variants.Results: Four heterozygous ADAR1 variants were identified, including two novel missense variants c.2369G>C (Arg790Pro), and 503C>T (Pro168Leu), and two previously reported variants: c.3232C>T(R1078C), and c.1472C>G (p.S491X). The novel c.503C>T variant was predicted as "deleterious" (score =− 2.704) by PROVEAN, and "probably damaging" (score = 1) by PolyPhen2. The other novel variant c.2369G>C was also predicted as "deleterious" (score =− 4.167) by PROVEAN, "probably damaging" (score = 1) by PolyPhen2, and "disease-causing" (p = 0.999) by Mutation Taster.Conclusion: Two novel ADAR1 variants were found in Chinese patients with DSH. This research has expanded the ADAR1 gene database for DSH, enhancing our comprehension of the underlying mechanisms.Keywords: dyschromatosis symmetrica hereditaria, adenosine deaminase acting on RNA1, mutation analysis, Chinese